Retraction: Lipid metabolism disturbances and AMPK activation in prolonged propofol-sedated rabbits under mechanical ventilation - JIANG Wei; YANG Zheng-bo; ZHOU Quan-hong; HUAN Xiang; WANG Li (Acta Pharmacologica Sinica, 2016)
The authors are retracting their article entitled “Lipid metabolism disturbances and AMPK activation in prolonged propofolsedated rabbits under mechanical ventilation” [Acta Pharmacol Sin 2012; 33: 27–33]. Several expressions of this article were identical to those of previously published paper by Dr Petros YPSILANTIS et al. [Anesth Analg 2007; 105: 155–66] and some original data were inappropriately manipulated. The authors would like to express their most sincere apology to Dr Petros YPSILANTIS and the Anesthesia & Analgesia and to the editors and readers of Acta Pharmacologica Sinica.